THE ANALYSIS OF GRAMMATICAL ERRORS SPOKEN BY MALANG TOURIST INFORMATION CENTER’S CUSTOMER SERVICES - Linda Setiorini (JURNAL ILMIAH BAHASA DAN SASTRA, 2017)
This research analyzes the grammatical errors in spoken English of customer services of Malang Tourist Information Center. The objectives of this research are to determine the types of errors and the cause of errors spoken by the customer services. The data were collected from four customer services by recording their conversation between them and the tourists. The study only focuses on the customer service’s utterances. The design of this research is descriptive qualitative research and the instrument is researcher herself. The finding of this research showed that the most dominant error was error of omission with 44 numbers (44%), followed by error of selection with 38 numbers (35%), error of ordering with 14 numbers (12%), and error of addition with 8 numbers (9%). The research also investigated that the causes of errors spoken by customer services were interlingua and intralingua transfer. Interlingua transfer was considered as the major cause of errors of customer services of Malang Tourist Information Center. Keywords: grammatical errors, error analysis, utterances